Exploring the Effectiveness of Blog Writing Technique in ESL Classrooms to Enhance the Writing Skills of Learners - Samarasinghe, A.G.S.M.; Abeyweera, G.H.; Herath, H.M.D.N.; Nayanahari, W.M.L.; Dissanayake, D.M.R.N.; Silva, R.R.P. (University of Jaffna, 2025)
In today’s highly competitive world, gaining competency in a second language is paramount for individuals since it has become one of the key elements of surviving and thriving in the industrial arena. Writing is indubitably a vital skill among the four basic skills that has to be mastered in the process of acquiring the English language. Yet, merely writing essays or answering questions in ESL classes does not facilitate the development of the learners’ writing skills in the target language. Additionally, the Generation Z learners detest traditional writing techniques and prefer techniques that are engulfed in modern technology. Thus, this study was conducted with the aim of investigating the efficacy of incorporating the Blog Writing technique to develop the writing skills of the undergraduates of the Faculty of Animal Science and Export Agriculture, Uva Wellassa University of Sri Lanka. The study was conducted using a mixed method of qualitative and quantitative methods. Primary data were retrieved via discussions, observations and unstructured interviews of a random sample of 50 undergraduates, whereas the secondary data were accumulated through previously published research in different contexts, books, journals and scholarly articles. The research was carried out for 15 weeks as the blog writing method was introduced and implemented for the second-year students at the beginning of their academic semester and the final formative assessment conducted at the end of the semester was considered for the study to investigate the effectiveness of practicing blog writing on their written skills. Apart from that, scripts produced at the beginning of the semester were compared with that of the scores obtained at the final formative written assessment to gain more insight. The findings of this study indicate that the majority of students have exhibited improvement in their writing tasks, while some undergraduates demonstrated a slight improvement. Considering the results accumulated through the study, it has become obvious that the implementation of the blog writing technique has a considerable positive impact on enhancing the writing skills of the students in ESL classrooms.
Keywords: Blog Writing Technique; Enhance; ESL Classrooms; Writing Skills